Suitability Analysis of Cross-sectional Interpolation for Calculating Water Surface Profile in Mountainous River Channels - CHENG Bei; HU Yuying (Renmin Zhujiang)
Calculating the water surface profile of river channels is an indispensable part of projects such as river channel management in mountainous areas. While the application of the HEC-RAS software developed in the United States in the calculation of river water surface profiles has been extensively studied, little attention has been paid to the impact of software cross-section interpolation on the calculation results when the distance between cross-sections in mountainous river channels is large and the number of cross-sections is limited. In this study, using HEC-RAS software and DEM elevation data of the mountainous river, Caishi River in Huairou District, Beijing, water surface profiles of the river for recurrence intervals of 10, 20, and 50 years are established under three scenarios including base cross-sections, interpolated cross-sections, and dense cross-sections. The results indicate that for mountainous river channels with relatively straight courses and little variation in cross-sectional forms and bed elevations, interpolation calculations can enhance accuracy. However, for mountainous river channels with irregular courses and significant variations in cross-sectional forms and bed elevations, interpolation calculations result in larger errors, and the uncertainty of recurrence intervals has an impact on water levels.